"A game of two halves?" Understanding the process and outcomes of English care home closures: Qualitative and quantitative perspectives. (19th June 2018) - Glasby, Jon; Allen, Kerry; Robinson, Suzanne
Abstract: With care services increasingly delivered via a market there is always a risk that care homes could fail financially or struggle in terms of quality, ultimately having to close. When this happens, the received wisdom is that subsequent relocation can be detrimental to the health and well‐being of older residents (possibly even culminating in increased mortality). However, there is very little formal evidence in the United Kingdom (UK) or beyond to guide policymakers and local leaders when undertaking such sensitive work. Against this background, this article reports findings from an independent evaluation of what is believed to be the largest care home closure program in the UK (and possibly beyond). This consisted of qualitative interviews with older people, families, care staff, and social work assessors during the closure process in one case study care home and one linked day center, as well as self‐reported health and quality of life data for older people from 13 homes/linked day centers at initial assessment, 28 days after moving and at 12‐month follow up. The study is significant in presenting public data about such a contested topic from such a large‐scale closure process, in its focus on both process and outcomes, in its mixed‐methods approach, and in its engagement with older people, families, and care staff alongside the use of more formal outcome measures. Despite significant distress part‐way through the process, the article suggests that outcomes either stayed the same or improved for most of our sample up to a year after moving to new services. Care homes closures may thus be a "tale of two halves", with inevitable distress during the closure but, if done well, with scope for improved outcomes for some people in the longer term. These findings are crucial for current policy and practice given that the risk of major closures seems to be growing and given that there is virtually no prior research on which to base local or national closure processes. While some of this research is specific to England, the underlying issue of care home closures and lessons learned around good practice will also apply to other countries.